Purification and Characterization of Two Proteins from Culture Filtrates of Mycobacterium tuberculosis H(37)Ra Strain - Daniel, Thomas M. (1970)
Two proteins have been purified from culture filtrates of Mycobacterium tuberculosis, H(37)Ra strain by a procedure combining gel filtration, diethylaminoethyl (DEAE)-cellulose chromatography, and zone electrophoresis. The two proteins are similar in molecular weight but differ slightly in charge. The faster migrating protein, designated a(1), is not antigenic. The slower migrating protein, designated a(2), is antigenic both with respect to antisera and as a skin-testing antigen.